Tracheo-oesophageal fistula after palliative treatment of oesophageal cancer - Hamer, Peter W. (J Gastrointest Oncol, 2015)
We present a case of an 86-year-old male who presented with severe pneumonia in the context of having undergone radiotherapy and then an oesophageal stent insertion for palliation of oesophageal cancer. He was diagnosed with a tracheo-oesophageal fistula (TOF) which was successfully managed by deploying a second stent within the first stent.